MEDIATING EFFECT OF CORPORATE IMAGE AND STUDENTS’ SATISFACTION ON THE RELATIONSHIP BETWEEN SERVICE QUALITY AND STUDENTS’ LOYALTY IN TVET HLIs - Sallaudin Hassan; Mohd. Farid Shamsudin; Muhammad Asyraf Hasim; Ishamuddin Mustapha; Jimisiah Jaafar; Khairul Firdaus Adruthdin; Athirah Shukri; Sunitawati Karim; Rohaizan Ahmad (Asian Academy of Management Journal, 2019)
The main purpose of this study is to investigate the mediation effect of corporate image and students’ satisfaction on the relationship between service quality and students’ loyalty in technical vocational and education and training (TVET) of higher learning institutes (HLIs). The respondents of this study were final year students from TVET HLIs in Malaysia. Using proportionate stratified sampling and followed by convenience sampling method, 431 questionnaires were distributed to nine higher TVET institutions. From that, 398 questionnaires were used for data analysis using SPSS version 22 and SmartPLS 3.0. The measurement model showed that the constructs were reliable and valid. Meanwhile, the structural model showed that there is a direct and significance relationship among all constructs. Two mediators were tested in this research which were service quality and corporate image. Bootstrapping procedure indicated that there was a direct and significant effect between latent constructs. The mediating test statistically showed that there was a partial mediation of student satisfaction and corporate image on the relationship between service quality and student loyalty. This research recommended that TVET HLIs should improve the level of service quality, corporate image, and satisfaction to ensure student satisfaction and loyalty.